Analysis of railway track deaths-an autopsy based study - K., Valsala; Sreedevi, C. S.; J., Sreelekshmi (International Journal of Research in Medical Sciences, 2017)
Background: Railway related deaths account for approximately one percentage of all fatalities submitted to medicolegal autopsies. The study is undertaken with the aim of better understanding of railway track deaths by analyzing the demographic details of victims and other contributing factors which favours the occurrence of railway track deaths. Methods: A cross sectional descriptive study of all railway track deaths brought for medicolegal autopsy at Thiruvananthapuram Medical College, Kerala, India from 1st March 2010 to 28th February 2011 was done. A total of 104 cases of railway track deaths were studied excluding cases with advanced decomposition. Clinical case records were studied in treated cases. details regarding nature dimensions and location of injury was entered in a proforma. The data were entered in MS Excel and statistical analysis was done. Results: Out of 104 cases studied 83 (79.8%) victims were male and 21 (20.2%) victims were female. The lowest and highest age of the victim involved in the study was 15 years and 90 years respectively. Elderly people with impairment of vision and hearing are most vulnerable to such accidents 12.5%. The highest frequency of incidence of railway deaths occurred while crossing the Railway track (32.7%), followed by jumping in front of the train (19.2%) and walking along the side or through track (16.3%). In 17.3% of the cases there was no exact history regarding the incident. The most common types of external injuries were lacerated wound and abrasion. In all the cases head showed lacerated wounds and the upper limbs showed abrasion. Conclusions: Present study concludes that majority of victims were males showing a female ratio 4:1, The peak incidence was noted in the 6th decade. Most of the victims were manual labourers. Travelling, moving and crossing near railway tracks in intoxicated condition is very usual practice. Survival period was found to be very less.